Disruption of the Microglial ADP Receptor P2Y13 Enhances Adult Hippocampal Neurogenesis - Stefani, Jennifer; Tschesnokowa, Olga; Parrilla, Marta; Robaye, Bernard; Boeynaems, Jean-Marie; Acker-Palmer, Amparo; Zimmermann, Herbert; Gampe, Kristine (Frontiers in Cellular Neuroscience, 2018)
In mammalian species, including humans, the hippocampal dentate gyrus is a primary region of adult neurogenesis. Aberrant adult hippocampal neurogenesis is associated with neurological pathologies. Understanding the cellular mechanisms controlling adult hippocampal neurogenesis is expected to open new therapeutic strategies for mental disorders. Microglia is intimately associated with neural progenitor cells in the hippocampal dentate gyrus and has been implicated, under varying experimental conditions, in the control of the proliferation, differentiation and survival of neural precursor cells. But the underlying mechanisms remain poorly defined. Using fluorescent in situ hybridization we show that microglia in brain express the ADP-activated P2Y13 receptor under basal conditions and that P2ry13 mRNA is absent from neurons, astrocytes, and neural progenitor cells. Disrupting P2ry13 decreases structural complexity of microglia in the hippocampal subgranular zone. But it increases progenitor cell proliferation and new neuron formation. Our data suggest that P2Y13 receptor-activated microglia constitutively attenuate hippocampal neurogenesis. This identifies a signaling pathway whereby microglia, via a nucleotide-mediated mechanism, contribute to the homeostatic control of adult hippocampal neurogenesis. Selective P2Y13R antagonists could boost neurogenesis in pathological conditions associated with impaired hippocampal neurogenesis.